A Comprehensive Chemical Model for the Splitting of CO2 in Non‐Equilibrium Plasmas. Issue 4 (17th October 2016) - Koelman, Peter; Heijkers, Stijn; Tadayon Mousavi, Samaneh; Graef, Wouter; Mihailova, Diana; Kozak, Tomas; Bogaerts, Annemie; van Dijk, Jan
Abstract : An extensive CO2 plasma model is presented that is relevant for the production of "solar fuels." It is based on reaction rate coefficients from rigorously reviewed literature, and is augmented with reaction rate coefficients that are obtained from scaling laws. The input data set, which is suitable for usage with the plasma simulation software Plasimo (https://plasimo.phys.tue.nl/ ), is available via the Plasimo and publisher's websites. The correctness of this model implementation has been established by independent ZDPlasKin implementation (http://www.zdplaskin.laplace.univ‐tlse.fr/ ), to verify that the results agree. Results of these "global models" are presented for a DBD plasma reactor. Abstract : A graphical overview of the complex CO2 chemistry, including the vibrational modes, which is implemented in the global models of Plasimo and ZDPlasKin. The reaction data set is obtained from literature and reviewed rigorously. The Plasimo compatible model, including the chemistry, is made available via the Plasimo (http://plasimo.phys.tue.nl/resources/index.html ) and the publishers websites.